2021
DOI: 10.1038/s41419-021-03896-1
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps impair intestinal barrier functions in sepsis by regulating TLR9-mediated endoplasmic reticulum stress pathway

Abstract: Increased neutrophil extracellular traps (NETs) formation has been found to be associated with intestinal inflammation, and it has been reported that NETs may drive the progression of gut dysregulation in sepsis. However, the biological function and regulation of NETs in sepsis-induced intestinal barrier dysfunction are not yet fully understood. First, we found that both circulating biomarkers of NETs and local NETs infiltration in the intestine were significantly increased and had positive correlations with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 48 publications
5
66
0
2
Order By: Relevance
“…Abundant neutrophils were activated to release NETs in the gut in lipopolysaccharide- (LPS-) induced sepsis [ 45 ]. Elevated serum NETs are associated with intestinal injury in abdominal sepsis patients [ 44 ]. Sun et al [ 44 ] suggested that NETs activated endoplasmic reticulum (ER) stress in the lethal septic shock model.…”
Section: Nets and Intestinal Injuries During Sepsismentioning
confidence: 99%
See 2 more Smart Citations
“…Abundant neutrophils were activated to release NETs in the gut in lipopolysaccharide- (LPS-) induced sepsis [ 45 ]. Elevated serum NETs are associated with intestinal injury in abdominal sepsis patients [ 44 ]. Sun et al [ 44 ] suggested that NETs activated endoplasmic reticulum (ER) stress in the lethal septic shock model.…”
Section: Nets and Intestinal Injuries During Sepsismentioning
confidence: 99%
“…Elevated serum NETs are associated with intestinal injury in abdominal sepsis patients [ 44 ]. Sun et al [ 44 ] suggested that NETs activated endoplasmic reticulum (ER) stress in the lethal septic shock model. TLR9 antagonist administration alleviated NET-induced damage in the intestinal epithelial cell monolayer through ER stress inhibition [ 44 ].…”
Section: Nets and Intestinal Injuries During Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in the bleomycin pulmonary fibrosis model, IRE1-a inhibition reduces alveolar epithelial apoptosis and prevented fibrosis (24,25). Recently, crosstalk between NETs and ER stress has been observed in a model of sepsisinduced intestinal injury, with inhibition of NETosis and ER stress reducing intestinal epithelial cell monolayer barrier disruption, suggesting that neutrophils and NETosis contribute to ER stress in intestinal epithelial cells (26).…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil extracellular traps (NETs) are a new antimicrobial function of neutrophils; NETs are web-like structures accompanied by many proteins, histones, and DNA [ 6 ]. The formation of NETs is a double-edged sword in sepsis; NETs trap pathogens in the early stage, while cause NETs-associated injuries, such as coagulation, thrombotic disorders, and organ injury, in the later stage [ 7 9 ]. The balance between NETs formation and clearance plays a crucial role in sepsis.…”
Section: Introductionmentioning
confidence: 99%